1991
DOI: 10.1007/bf00186867
|View full text |Cite
|
Sign up to set email alerts
|

Changes in C-reactive protein and erythrocyte sedimentation rate after hip fractures

Abstract: Serial measurements of C-reactive protein (CRP) levels and erythrocyte sedimentation rates (ESR) were performed during the week after operation in 140 patients with hip fractures. There was no selection, and patients with minor or major complications before or after operation were included. In uncomplicated cases, the ESR was variably raised during the first week, whereas the CRP showed a distinct pattern with a rapid increase on the second day; it then decreased by the 7th day. In cases with early postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 11 publications
0
18
1
1
Order By: Relevance
“…Previous studies (Ellitsgaad et al 1991, Choudhry et al 1992, Kragsbjerg et al 1995 have reported that CRP levels depend on the region of trauma, with the maximum levels on the second postoperative day. Reliable data exist for hip fractures (Okafor and Maclellan 1998) and arthroplasty of the hip (Niskanen et al 1996, White et al 1998, reaching values of about 10-16 mg/dL for standard procedures, using a posterolateral or anterolateral approach.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies (Ellitsgaad et al 1991, Choudhry et al 1992, Kragsbjerg et al 1995 have reported that CRP levels depend on the region of trauma, with the maximum levels on the second postoperative day. Reliable data exist for hip fractures (Okafor and Maclellan 1998) and arthroplasty of the hip (Niskanen et al 1996, White et al 1998, reaching values of about 10-16 mg/dL for standard procedures, using a posterolateral or anterolateral approach.…”
Section: Discussionmentioning
confidence: 91%
“…CRP levels normally rise within 2 to 6 hours after surgery and then go down by the third day after surgery. Ellitsgaard et al conducted a study (on 140 elderly patients with hip fractures) that measured CRP and ESR during the week after the operations 7) . The postoperative ESR in uncomplicated cases remained elevated 1 week after surgery, while the CRP peaked at day 2 and normalized by day 7.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that CRP is a sensitive parameter in monitoring orthopedic postop complications (13,14). However, conflicting data exist regarding the value of IL-6 in monitoring orthopedic postop complications (12,15).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Giannoudis and colleagues (12) studied orthopedic blunt trauma victims, and concluded that early assessment of CRP and IL-6 was not beneficial in diagnosing sepsis and that their levels following trauma should be assessed with caution. Ellitsgaard and colleagues (13) studied 140 hip-fracture-operated patients and found high serum CRP levels in postop bronchopneumonia and deep wound infections.…”
mentioning
confidence: 99%